The Effect of Taxpayer Awareness, Service Quality, Tax Sanctions, Tax Knowledge, and Tax Socialization on Taxpayer Compliance in Paying Motor Vehicle Taxes (Case Study on SAMSAT Pati Regency) - Wijiyanti Wijiyanti; Tutik Dwi Karyanti; Marliyati Marliyati (Applied Accounting and Management Review (AAMAR), 2022)
Study this aim to get empirical proof about the influence of Awareness Required Tax, Quality Service, Penalty Taxation, Knowledge Tax, And Socialization Taxation To Obedience Required Tax In Pay Tax Vehicle Motorized. This type of study uses a quantitative approach. Sample in study this as much 100 respondents with Random Sampling technique. Test Validity and Test Reliability used for test instrument study. On testing normality data use Test Normality, Test Multicollinearity and Test Heteroscedasticity. On testing hypothesis use Test Analysis Regression linear multiple in the form of Test Coefficient Determination , Test Partial and Test Simultaneous. Results from study this show that by Partial awareness Required tax, quality service, penalty taxation, knowledge tax, and socialization taxation take effect to obedience Required tax in pay tax vehicle motorized. Whereas by simultaneous show that awareness Required tax, quality service, penalty taxation, knowledge tax, and socialization taxation by together take effect to obedience Required tax in pay tax vehicle motorized.